A blueprint for an energy policy in Greece with considerations of climate change. (15th January 2016) - Chatzizacharia, Kalliopi; Benekis, Vasilis; Hatziavramidis, Dimitris
Highlights: Climate change and energy variables for Greece are forecasted for the next 25 years. Aforementioned variables are cointegrated to check causality and stationarity. Power generation by methods of reduced CO2 emissions is set as optimization problem. Energy production with wind power and lignite with zero-emissions option is optimal. Abstract: An approach for a plan to meet the energy needs of the state of Greece in conjunction with assumed responsibilities to confront global warming is presented. Time series of climate indicators like average temperature and rain precipitation together with energy consumption and CO2 emissions are examined for stationarity and causality. Predictions of energy needs for the next 25 years and CO2 emissions are made. With these predictions, production of energy from renewable sources like wind turbines and photovoltaic panels as well as from lignite with CO2 capture and sequestration systems attached to power-generating units is formulated as an optimization problem with financial and environmental constraints.